Clinical features, disease burden and impact on quality of life in participants with mitochondrial encephalomyopathy - John Sieh Dumbuya; Chuan Tian; Lin Deng; Bashir Ahmad; Xiuling Chen; Jun Lu (Frontiers in Neurology)
BackgroundMitochondrial encephalomyopathy (ME) is a rare genetic disorder that significantly impacts participants’ quality of life and places emotional and financial burdens on caregivers. However, the dynamics between perceived financial burden, disability, and caregiver strain are not fully understood. This study aimed to explore the differences in perceived financial burden, QoL, disability levels, and caregiver burden among participants with ME.MethodsBetween January and December 2023, we conducted a cross-sectional analysis of ME participants and their caregivers at Haikou Affiliated Hospital of Xiangya Medical College, Central South University. Multiple assessment scales, including CHU-9D, PedsQL, PHQ-9, and CBI, were used to evaluate disease burden, QoL, disability, and caregiver burden. Descriptive statistics and correlation coefficients were employed to assess the relationships between these factors.ResultsA total of 27 participants with ME were identified, with a mean age of 10.14 years, 88.9% of whom were children. The cohort comprised 18 (66.7%) males and 9 (33.3%) females; MELAS and Leigh syndrome were the most common subtypes. Significant correlations were found between QoL scores and caregiver burden, with CHU-9D showing negative correlations with PHQ-9 and CBI and positive correlations with PedsQL and health utility scores. Additionally, 44.4% of participants reported severe financial burdens, and 57.7% of caregivers experienced moderate to severe levels of burden.ConclusionOur findings highlight the complex relationships between financial strain, QoL, and caregiver burden in ME. This underscores the need for comprehensive, patient-centered care and targeted policy interventions to alleviate patient and caregiver burdens. Further research is essential to develop effective support systems and improve overall outcomes.